THE PROCESS OF DEVELOPING ELECTRIC CARS CONVERSION TRAINING FOR MECHANICAL: A NEED ANALYSIS - Musida, Meis; Hanafi, Ivan; Sukardjo, Mochammad (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
The The increasing availability of electric cars in recent years is one of the impacts of shrinking energy sources. This development is a challenge for automotive training institutions. Even though the government has issued regulations regarding converting cars to electric car, automotive training institutions dedicated to electric vehicle conversion training still need to be established. Based on the data collected, the target is 1.000 conversion workshops certified by the end of 2023; however, until this article was written, only 24 conversion workshops had received certification. A preliminary study analysis of mechanical training needs in electric car conversion workshops is presented in this paper. The goal is to improve teaching and maximize areas of mechanical proficiency. Interviewing various people related to the automotive industry and potential buyers of electric cars is a qualitative research method. Research findings regarding sustainable professional growth's current and future conditions assist competency improvement and development. The interviewee assessed the importance of providing effective and efficient electric car conversion training, assisted by digital technology, as part of the educational process and chose the flipped classroom model.